Learning Model Higher Order Thinking Skills at Vocational High School: Achievement and Thinking Behavior - Yusuf, Slamet. P. H., Thomas Sukardi , Mohd. Khairudin (International Journal of Advanced Science and Technology, 2020)
The purpose of this study is to promote learning model of Higher Order Thinking Skills that can improve students’ achievement, easy to implement and to adapt the supporting of existing tools and materials. The evaluation effect of the application Higher Order Thinking Skills learning model produced the aspect of critical thinking skills, creative thinking and students’ problem solving. The approach used in this study was Research and Development. Preliminary research data was collected through interviews, class observations and documents analysis. The trial data were obtained by quasi experiments. The research data were analyzed by qualitative analysis techniques for interview data and quasi-experimental data were analyzed quantitatively. The results of study indicate that the Higher Order Thinking Skills learning model was proven to be effective improving the achievement students with an effectiveness level of 73%, and the ability to think critically, creative thinking and problem solving students with an effectiveness level of 80%. The learning model developed as an alternative in teaching and learning activities has quite high effectiveness.